2011
DOI: 10.1093/heapro/dar037
|View full text |Cite
|
Sign up to set email alerts
|

'Trying to make it all come together': structuration and employed mothers' experience of family food provisioning in Canada

Abstract: This research examined the aetiology of employed mothers' food choice and food provisioning decisions using a qualitative, grounded theory methodology. Semi-structured interviews using the Food Choice Map were conducted with eleven middle-income employed mothers of elementary school-age children. Results demonstrated that the women exhibited conflicting identities with respect to food choice and provisioning. As 'good mothers' they were the primary food and nutrition caregivers for the family, desiring to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 30 publications
2
62
0
1
Order By: Relevance
“…Dual parental and employment responsibilities may induce stress among mothers and modest evidence suggests that adverse mental health (e.g. depression) is associated with increased overweight among women [43][44][45][46]. It is possible that the rapid transformation of the food and built environment in LMIC, such as the spread of supermarkets and availability of ultra-processed foods, provides an enabling environment for the aforementioned hypothesized changes among formally employed women [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Dual parental and employment responsibilities may induce stress among mothers and modest evidence suggests that adverse mental health (e.g. depression) is associated with increased overweight among women [43][44][45][46]. It is possible that the rapid transformation of the food and built environment in LMIC, such as the spread of supermarkets and availability of ultra-processed foods, provides an enabling environment for the aforementioned hypothesized changes among formally employed women [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these foods are often high in fat and sugar and children become accustomed to them, hence developing a preference. [26,27] This could result in the younger generations acquiring fewer cooking skills from their mothers and, in turn, a reliance on convenience foods.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Not only is there a need for healthier pre-prepared and convenience meals, but also for the education of mothers on ways to prepare quickand-easy nutritious homemade meals. The food industry has responded and capitalised on this need, but the majority of options still focus on convenience and not on health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women with lower incomes are less able to achieve normative ideals of food provisioning, enact and maintain identity through food provisioning, and provide care and nourishment for their loved ones, adding to the potential stresses of food provisioning [44]. Further, research has found that women often make trade-offs between their preferred food provisioning practices and the constraints they experience, and using convenience foods is a common strategy that can minimize the physical and mental labor of food provisioning [45,46], potentially even for women who would prefer to engage in LFSs.…”
Section: The Importance Of Food Assistance For Womenmentioning
confidence: 99%